English English - SEPTIANO, ALVIN; Andayu, Haryasena Gusti; Maulana, Imam (Kreator, 2024)
This research aims to characterize the optical properties of bioplastic packaging based on a mixture of cassava starch and lead acetate as an alternative material for X-ray radiation protection. The experimental method was used by varying the composition of a mixture of cassava starch and lead acetate in ratios of 100:0, 70:30, 65:35, 60:40, 55:45, 50:50, and 45:55. Optical characterization was carried out using UV-Vis spectrophotometry to measure the absorbance, reflectance and transmittance of the sample. The results show that samples with higher lead acetate concentrations have greater absorbance, especially in the UV range, as well as lower transmittance throughout the spectrum. Samples with ratios of 45:55 and 50:50 (cassava starch:lead acetate) showed the best potential as radiation shielding due to high absorbance and low transparency. This research provides a comprehensive understanding of the optical properties of a mixture of cassava starch and lead acetate, enabling composition optimization for specific applications in X-ray radiation protection.